You are on page 1of 6

# AMATH 231

## ASSIGNMENT # 9 Stokes Theorem

Fall 2014

Due Monday, November 24, 2014 at 2pm in box 7, slot 11 (A-M) and 12 (N-Z), located
across from MC4066. Late assignments or assignments submitted to the incorrect dropbox
deducted for poor presentation and incorrect notation.
H
1. Compute the circulation C F~ d~x directly and then use Stokes theorem to verify your
answer: let F~ (x, y, z) = ((x + 1)2 , 0, x2 ) and C is the intersection of the cylinder
x2 + 2x + y 2 = 3 and the plane z = x oriented counter clockwise as seen from above.
[4 marks]
Solution:
The cylinder can be written as (x + 1)2 + y 2 = 4. The intersection between the cylinder
and the plane is,
~g (t) = (2 cos t 1, 2 sin t, 2 cos t 1),

t [0, 2].

## Therefore the derivative is,

~g 0 (t) = (2 sin t, 2 cos t, 2 sin t),

t [0, 2].

## This allows us to compute the circulation directly:

Z
Z 2
~
F d~x =
(4 cos2 t, 0, (2 cos t 1)2 ) (2 sin t, 2 cos t, 2 sin t) dt,
~g

## (8 cos2 t + 8 cos2 t 8 cos t + 2) sin t dt,

Z0 2
(8 cos t sin t + 2 sin t) dt,

2
= 4 cos2 t 2 cos t 0 ,
=

= 0.
Next, we parameterize the plane inside the cylinder using,
~ v) = (u, v, u),
S(u,

where (u + 1)2 + v 2 4. The upward unit normal to the plane is (1, 0, 1)/ 2. The
~ F~ = (0, 2x, 0).
curl is
If we apply Stokes theorem we get,
Z
ZZ
~
~ F~ ) n
F d~x =
(
d,
~g

ZZ

=
(0, 2x, 0) (1, 0, 1)/ 2 d,

= 0.

H
2. Compute the circulation C F~ d~x directly and then use Stokes theorem to verify
your answer: let F~ (x, y, z) = (2y, z, z) and C is the intersection of the cylinder
x2 + z 2 = 1 and the plane y = x + 1 oriented counter clockwise as seen from the origin.
[4 marks]
Solution:
The intersection between the cylinder and the plane is,
~g (t) = (cos t, cos t + 1, sin t),

t [0, 2].

## Therefore the derivative is,

~g 0 (t) = ( sin t, sin t, cos t),

t [0, 2].

## This allows us to compute the circulation directly:

Z 2
Z
~
(2(cos t + 1), sin t, sin t) ( sin t, sin t, cos t) dt,
F d~x =
0

~g

## (2 cos t sin t + 2 sin t sin2 t cos t sin t) dt,

=
0

1
(cos t sin t + 2 sin t (1 sin 2t)) dt,
2
0

2
1 2
1
1
=
sin t 2 cos t t cos 2t
,
2
2
4
0
= .
=

## Next, we parameterize the plane inside the cylinder using,

~ v) = (u, u + 1, v),
S(u,
~
~
The tangent vectors are S/u
= (1, 1, 0) and S/v
= (0, 0, 1) so the normal vector
~
is N = (1, 1, 0)
~ F~ = (1, 0, 2).
The curl is
If we apply Stokes theorem we get,
Z
ZZ
~
~ F~ ) n
F d~x =
(
d,
~g

ZZ
=
(1, 0, 2) (1, 1, 0) dudv,

ZZ
=
1 dudv,

= .
In the last line we used the fact that the area of the circle is since the radius is one.

3. Let F~ be a constant vector field. A surface in R3 and its boundary curve ~g are
assumed to satisfy the assumptions of Stokes Theorem. Show that
ZZ
Z
1
~
F n
d =
(F~ ~x) d~x,
2

~g
where ~x = (x, y, z). Hint: start with the right hand side. [2 marks]
Solution:
We start wit the RHS and use Stokes theorem:
Z
ZZ h
i
1
1
~
~ (F~ ~x) n
(F ~x) d~x =

d
2 ~g
2
To evaluate the integrand we first compute the cross product assuming that F~ is
constant:
F~ ~x = (F2 z F3 y, F3 x F1 z, F1 y F2 x).
Then we compute the curl of this,
~ (F~ ~x) = (F1 + F1 , (F2 F2 ), F3 + F3 ) = 2F~ .

## We plug this into our above expression and get,

Z
ZZ
1
~
(F ~x) d~x =
F~ n
d,
2 ~g

as desired.

4. Show that if the boundary curve and the surface satisfy the assumptions of
Stokes theorem then
a)
ZZ 

~ g
~
f
n
d =

~ d~x.
f g

b)
Z

~ d~x = 0.
f f

~g

Solution:

a) We begin with the RHS, use Stokes theorem and then using vector identities,
I
ZZ h
i
~
~ (f g)
~
f g d~x =

n
d,

ZZ h
i
~ (g)
~ + (f
~ g)
~
f
n
d,
=

ZZ 

~
~
=
f g n
d,

as desired.
b) Begin with the equation in part a) and set g = f ,
I
ZZ 

~ d~x =
~ f
~
f f
f
n
d,

= 0,
because the curl of any vector with itself is zero.

## 5. Consider Maxwells equations with no density charge and no current.

a) Take the curl of Faradays law and obtain (for some constant c)
~
2E
~
= c2 2 E.
2
t
b) Take the curl of Amp`eres law and obtain (for some constant c)
~
2B
~
= c2 2 B.
t2
c) The constant c is the speed at which the solution propagates. What is c?


~
~ F~ =
~
~ F~ 2 F~ .
Note the identity
~
E
t
~
H
t
~
~
E
~ H
~

~ H,
~
= c
~ E,
~
= c
= 0,
= 0.

[3 marks]
Solution:
a) Compute the curl
~
~
~ E
~ =
~ B ,

~ =
~ B,
~
2 E
t
2
~
~ = 0 0 E.
2 E
t2
b) Take the curl of Amp`eres law and obtain
~
~
~ B
~ = 0 0
~ E ,

~ = 0 0
~ E,
~
2 B
t
2
~ = 0 0 B.
~
2 B
t2
c) We have c2 = 0 0 .

6. In a Perfect Fluid the pressure, p(~x, t) experts a force per unit area on a surface given
by pij n
j times the surface element. Note that this is the force in the ei direction
due to the surface in the n
j direction. Gravity exerts a force per unit mass on the fluid
given by the constant vector ~g (gravitational acceleration). Furthermore, we define
(~x, t) to be the density per unit volume and ~u(~x, t) to be the velocity.
a) Newtons second law states that the time derivative of the total momentum is
equal to the sum of the forces. Use this principle to derive the following identity,
ZZZ
ZZZ
ZZ
d
~u dV =
~g dV
pij n
j d.
dt
V
V

## where V (t) is the volume and (t) is the surface boundary.

b) Use Gauss Divergence Theorem to rewrite the pressure term as a triple integral
in the equation from part a).
c) In the case where the volume is moving one needs to use a more general theorem
called the Reynolds Transport theorem, which states,
ZZZ
ZZZ
f
d
~ (~uf ) dV
f dV =
+
dt
t
V
V
Use this theorem and our lemma from class to obtain a differential equation that
describes the motion of a perfect fluid. This equation is called the Navier-Stokes
equation and governs virtually all fluid motions.
Solution:
a) The LHS is the time derivative of the total momentum of the fluid. The RHS is
a sum of two forces: the total force due to gravity and the total force due to the
pressure. where V (t) is the volume and (t) is the surface boundary.
b) Apply Gauss theorem
ZZ
ZZZ
pij n
j d =

(pij ) dV =
xj

ZZZ
V

(p) dV =
xi

ZZZ

~ dV
p
V

c) We plug part b) into part a) and use the transport theorem on the LHS
ZZZ
ZZZ
ZZZ
(ui ) ~
p
+ (~uui ) dV =
gi dV
dV.
t
V
V
V xi
These can be combined into one integral

ZZZ 
(ui ) ~
p
+ (~uui ) gi +
dV = 0.
t
xi
V
By our lemma we deduce that the integrand is zero,
(~u) ~
~
+ (~u~u) = ~g p.
t